Cartilage destruction in rheumatoid arthritis, its association with functional impairments - Natalia Vladimirovna Chichasova (Современная ревматология)
The paper discusses the mechanisms of destructive processes in rheumatoid arthritis (RA). At the present stage, in addition to suppress inflammation, the goals of treatment are to prevent cartilage and bone destruction in the affected joints. Prediction of destructive processes in RA plays an important role as the irreversibility of functional changes in RA directly correlates with the degree of joint injury. The paper discusses the mechanisms of articular cartilage and bone destruction and the significance of different biochemical markers for estimating the degree of injury and for predicting further destruction of small hand and foot joints. In RA, the investigators identify not only clinical (activity indicators), but also biological (bone, cartilage, and synovium damage markers) predictors for joint injury: CТXII is a marker for cartilage degradation (collagen type II) and CTXI is a marker for bone degradation (collagen type I) and their trends over 4–12 or more weeks. Although the occurrence of erosions is considered to be a major manifestation of joint destruction progression in RA, the functional activity in its early stages is shown to depend on the estimate of joint space narrowing (cartilage degradation) to a greater extent than on that of erosions when evaluating the destruction by the modified Sharp method. Several randomized placebocontrolled studies (RPCSs) have assessed the association of patients' functional capacity with joint space narrowing or with the number of erosions. In RA, cartilage degradation has been demonstrated to play a larger role in irreversible function loss than bone destruction.The possibility of suppressing cartilage degradation, which is indicated in RPCSs of the efficacy of adalimumab, correlates with a better functional outcome in patients with RA. Serum markers for cartilage metabolism may be not only predictors for further radiographic progression, but also be used to evaluate therapeutic effectiveness.